The outcome of ulcerative colitis patients undergoing pouch surgery is determined by pre‐surgical factors. Issue 5 (30th June 2017) - Yanai, H.; Ben‐Shachar, S.; Mlynarsky, L.; Godny, L.; Leshno, M.; Tulchinsky, H.; Dotan, I.
Summary: Background: Pouch surgery, a common intervention for ulcerative colitis (UC) complications, is often associated with the development of pouchitis. Aim: To identify predictors of pouch outcome in a cohort of patients with UC. Methods: We conducted a retrospective unmatched case‐cohort study in a tertiary IBD referral centre. Adult patients with UC were classified into the worst phenotype throughout follow‐up: normal pouch, a form of chronic pouchitis (either chronic pouchitis or Crohn's like disease of pouch [CLDP]), or episodic recurrent acute pouchitis (RAP). Risk factors for pouchitis (chronic forms) were detected using statistical models. Results: Two hundred and fifty‐three pouch patients were followed up for 13.1±7.3 years. Only 71 patients (28.1%) maintained a favourable outcome of a sustained normal pouch. These patients were older at UC diagnosis (27.8±12.5 vs 23.0±11.4 years), had longer UC duration until surgery (13.4±9.5 vs 8.2±7.9 years), and had higher rates of referral to surgery due to nonrefractory (dysplasia/neoplasia) complications (42.3% vs 16.2%) compared with pouchitis patients. Median survival for sustained normal pouch was 10.8 years (95% CI 8.9‐12.7 years), and it was longer in the nonrefractory group (20.3 vs 9.4 years for the refractory group, HR=2.37, 95% CI 1.25‐3.52, P =.004). Conclusions: Most patients with UC undergoing pouch surgery will develop pouchitis. Patients operated for nonrefractory indications have a more favourable outcome. These results may contribute to pre‐ and post‐surgical decision‐making. The findings imply that the processes determining UC severity may be similar to that causing pouchitis. Abstract : Linked Content This article is linked to Ayubi et al and Safiri and Yanai papers. To view these articles visithttps://doi.org/10.1111/apt.14255 andhttps://doi.org/10.1111/apt.14289 .